The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1046/j.1365-2788.1998.00146.x
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the Mini PAS‐ADD for assessing psychiatric disorders in adults with intellectual disability

Abstract: The Mini PAS-ADD is an assessment schedule for psychiatric disorders in people with an intellectual disability. It is designed to provide a link between the mental health expertise of psychiatrists and psychologists, and the detailed knowledge of individual service users possessed by support staff. In broad terms, the aim of the Mini PAS-ADD is to enable non-psychiatrists accurately to recognize clinically significant psychiatric disorders in the people who they care for, so that they can make informed referra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
108
2
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(115 citation statements)
references
References 6 publications
1
108
2
4
Order By: Relevance
“…Adult participants were interviewed using the Structured Clinical Interview for Axis I DSM-IV (SCID) 28 in 9 centers and the PAS-ADD clinical interview for adults 29 in one center (Cardiff). Psychiatric diagnoses were established, when appropriate, according to the fourth edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-IV).…”
Section: Psychiatric Evaluationmentioning
confidence: 99%
“…Adult participants were interviewed using the Structured Clinical Interview for Axis I DSM-IV (SCID) 28 in 9 centers and the PAS-ADD clinical interview for adults 29 in one center (Cardiff). Psychiatric diagnoses were established, when appropriate, according to the fourth edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-IV).…”
Section: Psychiatric Evaluationmentioning
confidence: 99%
“…The more recent Psychiatric Assessment Schedule for Adults with a Developmental Disability (PAS-ADD; Moss et al, 1993b), developed by the Hester Adrian Research Centre, has been shown to have both reasonable reliability and validity (Costello et al, 1997;Moss et al, 1997Moss et al, , 1998Prosser et al, 1998). This makes it one of the most useful tools currently available for the identification and diagnosis of psychiatric disorder in adults with learning disability.…”
Section: The Pas-addmentioning
confidence: 99%
“…43 Current mental health status was assessed using the PAS-ADD interviews. 44 The data gathered were used to confirm inclusion and exclusion criteria. If required, clinical review was undertaken for those exceeding thresholds for the ABS (a score that converts to an estimated IQ of > 70 using the method described by Moss and Hogg…”
Section: Screening Measurementioning
confidence: 99%